2020
DOI: 10.1002/adom.201902024
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Light Emission by Magnetic and Electric Resonances in Dielectric Metasurfaces

Abstract: An enhanced emission of high quantum yield molecules coupled to dielectric metasurfaces formed by periodic arrays of polycrystalline silicon nanoparticles is demonstrated. Radiative coupling of the nanoparticles, mediated by in‐plane diffraction, leads to the formation of collective Mie scattering resonances or Mie surface lattice resonances (M‐SLRs), with remarkable narrow line widths. These narrow line widths and the intrinsic electric and magnetic dipole moments of the individual Si nanoparticles allow reso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
84
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 74 publications
(89 citation statements)
references
References 63 publications
4
84
1
Order By: Relevance
“…For our hybrid system, nanopillar arrays are on an optically thick metal film, which blocks the transmission of light completely, and the issue of symmetric dielectric environment between the substrate and the upper cladding does not exist, in contrast to the requirement of a symmetric environment for achieving sharp lattice resonances in all-plasmonic [14,16] and alldielectric systems. [15,17] In this work, we show that dielectric nanopillar arrays on metal can be an efficient platform for refractometric sensing. We fabricate TiO 2 nanopillar arrays on gold by reactive ion etching (RIE) combined with a large-area soft lithography technique.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…For our hybrid system, nanopillar arrays are on an optically thick metal film, which blocks the transmission of light completely, and the issue of symmetric dielectric environment between the substrate and the upper cladding does not exist, in contrast to the requirement of a symmetric environment for achieving sharp lattice resonances in all-plasmonic [14,16] and alldielectric systems. [15,17] In this work, we show that dielectric nanopillar arrays on metal can be an efficient platform for refractometric sensing. We fabricate TiO 2 nanopillar arrays on gold by reactive ion etching (RIE) combined with a large-area soft lithography technique.…”
mentioning
confidence: 76%
“…The collective lattice resonance stemming from the diffractive coupling in a periodic array of either metal [ 10–12 ] or high‐index dielectric nanoparticles [ 13 ] requires a symmetric refractive‐index environment between the bottom substrate and the upper cladding (e.g., aqueous buffers in sensing). [ 14–17 ] An asymmetric environment can inhibit long‐range coupling between nanoparticles and suppress lattice resonances. In optical sensing, a periodic array of either metal or high‐index dielectric nanoparticles is usually fabricated on a transparent substrate and exposed to solutions with different refractive indices.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…This is aligned with previous reports that showed that in periodic arrays of Si nanoparticles, SLR occurs more efficiently in homogeneous media. [ 33,34 ] In fact under this condition, the first‐order RA wavelength, given by λRA=n×D (n=nsup or nsub), influences the wavelength of the sharp peak. Therefore, to tune the wavelength of SLR, one needs to change nsup and nsub consistently.…”
Section: Lattice‐induced Coherent Coupling Of Si Ncsmentioning
confidence: 99%
“…Recent studies have shown the possibility of hybridization of magnetic and electric dipoles of Si nanoparticles with the lattice modes, forming SLRs associated with diffractive coupling of such dipoles with the Rayleigh anomaly (RA). [ 26,32–34 ]…”
Section: Introductionmentioning
confidence: 99%